PENGARUH MENTAL IMAGERY TERHADAP KEMAMPUAN SISWA DALAM PENGUASAAN TEKNIK DASAR DRIBBLE BOLA BASKET DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN - LUKMAN ARIF, PRADANA (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract . In the physical education learning, the must important that connected with the consist of learning process effectively  are the ability of teacher to combine various learning situation into learning activity, the combining of those learning condition in a form of learning method. . In this matter the researcher have alternative with giving the practice of mental  imagery to students. Mental imagery is an ability of people to build a motion image or a skill in the mental or mind. Researcher want to knowing the effect of mental  imagery to student ability in mastering basket ball dribble basic technique in the physical education and health. This research is a quasi experimental research, the data analysis with using normality test, homogeneities test  and t test. Population in this research are the whole seventh grade student of SMP Negeri 1 Ngunut Tulungagung lesson year 2009/2010 with amount of 347 that divided to eight class. Sample intake with using cluster sample namely class of VII B as experiment group with amount  of 39 student, and class VII C as a control group with amount of 40 student. From this research can be conclude that the utilization of mental imagery practice have a significant effect to the ability of student in mastering the basic technique of basket ball dribble, it can be seen from the average pretest result  34.30 and post test average 21.28 and the difference of pretest average with posttest average are 13.02 that mean there is an improvement of the ability of dribble as big as 37.97%  in the experiment group. From the t test result get signification score is 0.990 this score is bigger than alpha (α= 0.05) with the result that the hypothesis can be accept. Keywords: mental imagery, mastering basket ball dribble